CONTRACEPTIVES RELATED TO UTERINE CANCER - Muhammad Haris Baig; Muhammad Hashim; Muhammad Huzaifa; Dr Fazal Hanan; Muhammad Aafaq Bashir; Izza Rafique; Muhammad Qamar; Muhammad Junaid Afzal; Dr Farah Abid; Muhammad Atif (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The uterine lining, or endometrium, serves as where uterine cancer, often referred to as cancer of the endometrium, begins. It is the type of uterine cancer which damage women’s reproductive systems the most frequently. Methods: Application of different hormonal and non-hormonal contraceptives on uterine cancer. Results: Obesity, diabetes, hormonal imbalances (such as high estrogen), and a family history of the illness are risk factors for uterine cancer. Conclusions: It has been showed that combined oral contraceptives, which contain both progestin and estro-gen, lower the risk of uterine cancer by controlling hormone levels , which reduces the endometrium’s exposure to estrogen.